The suitability of local accounting systems and the requirements of the International Accounting Standard in the public sector (IPSAS 24): A government accounting system as a mod (Entrepreneurship Journal for Finance and Business, 2023)
It aims to analyze, study and discuss the shortcomings of the accounting system, and to achieve this, the descriptive analytical approach was adopted to study the accounting system and determine its main dialogue and its consistency with the requirements of the International Accounting Standard in the Public Sector (IPSAS24) in order to increase the effectiveness of the government accounting system applied in economic units through the use of  The relevant international accounting standards, and the research reached a number of conclusions, including those that the government accounting system relies on in recognizing financial transactions and events on the cash basis. Thus, the elements of the financial statements consist of cash receipts, cash payments and cash balances. Because of this basis, the results of the years’ business overlap and may encourage  This is on waste, as government units spend their allocations at the end of the fiscal year randomly so that they are not returned to the treasury،The research has several recommendations, including the need to apply the (IPSAS24) standard in government units, through which budget information is presented in the financial statements in order to achieve the qualitative characteristics of the financial statements, in addition to the statement of deviations and their causes and finding the necessary treatments for proper planning of the general budget.